2021
DOI: 10.1097/psy.0000000000001012
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay Between Stress and Fullness in Patients With Functional Dyspepsia and Healthy Controls: An Exploratory Experience Sampling Method Study

Abstract: ObjectiveFullness is a cardinal symptom in functional dyspepsia (FD). The use of real-time symptom assessment might provide more insight into factors, such as daily stress, that can influence fullness. Therefore, this study aimed to use the experience sampling method (a real-time, repeated-measurement method making use of repeated questionnaires available at random moments for a limited amount of time) to assess the association between stress and fullness in patients with FD and healthy controls (HCs).MethodsT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
4
1
Order By: Relevance
“…Our study supports other studies showing stress to be associated with FSS, 18,19 functional somatic symptoms, 53,54 chronic fatigue syndrome, 55 fibromyalgia, 56,57 irritable bowel syndrome, 58 and functional dyspepsia. 59 Generally, we found that perceived stress was higher in individuals with FSD than in healthy individuals; however, we could not support the hypothesis of equivalence in perceived stress between individuals with FSD and individuals with a severe physical disease, as the latter had lower perceived stress. However, compared to individuals with severe physical disease and an FSD, we found equivalent levels of perceived stress.…”
Section: Discussioncontrasting
confidence: 80%
“…Our study supports other studies showing stress to be associated with FSS, 18,19 functional somatic symptoms, 53,54 chronic fatigue syndrome, 55 fibromyalgia, 56,57 irritable bowel syndrome, 58 and functional dyspepsia. 59 Generally, we found that perceived stress was higher in individuals with FSD than in healthy individuals; however, we could not support the hypothesis of equivalence in perceived stress between individuals with FSD and individuals with a severe physical disease, as the latter had lower perceived stress. However, compared to individuals with severe physical disease and an FSD, we found equivalent levels of perceived stress.…”
Section: Discussioncontrasting
confidence: 80%
“…Indeed, the involvement of mast cells in the emergence of a barrier defect following peripheral CRH administration was corroborated in healthy controls since it could be blocked by pretreatment with cromoglycate, a mast cell stabilizer, while a strikingly similar effect was observed in response to acute psychological stress ( Vanuytsel et al, 2014 ). Functional dyspepsia patients also reported higher stress levels accompanied by increased fullness, a critical FD symptom, compared to healthy controls, and both were positively associated with one another in patients but not controls ( Klaassen et al, 2021 ). This suggests a direct relationship between stress and FD symptoms, in which increased duodenal eosinophil and mast cell numbers may play a role.…”
Section: Factors Related To Immune Activationmentioning
confidence: 99%
“…For its role in FD, occupational stress or burnout was found to be associated with FD among female employees ( Nam et al, 2018 ). Additionally, patients with FD had higher levels of stress compared with healthy controls; there was also a positive correlation between preceding and concurrent stress and the severity of fullness, a cardinal symptom of the FD ( Klaassen et al, 2022 ). The authors conclude that elevated stress levels may precede fullness sensations in patients with FD ( Klaassen et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%